A multi-centre analysis of adjuvant contact X-ray brachytherapy (CXB) in rectal cancer patients treated with local excision – Preliminary results of the CONTEM1 study. (September 2021) - Dhadda, Amandeep; Sun Myint, Arthur; Thamphya, Brice; Hunter, Iain; Hershman, M.; Gerard, Jean-Pierre
Highlights: This is the largest multi-centre cohort of rectal cancer patients treated with local excision and adjuvant contact X-ray brachytherapy. Local recurrence for early rectal cancer patients with adverse pathological features following local excision and treated with adjuvant contact X-ray brachytherapy was 9% at 6 years with long term follow up. Local recurrence is highly associated with development of distant metastatic disease. Organ preservation was achieved in 95% of patients with excellent oncological outcomes. Long term follow up of patients is required due to unusual late local recurrence. Abstract: Introduction: Early rectal cancers are increasingly diagnosed through screening programmes and are often treated using local excision (LE). In the case of adverse pathological features completion total mesorectal excision surgery (TME) is the standard recommendation. The morbidity and mortality risks of TME have stimulated the use of adjunctive treatments following LE to achieve organ preservation. Material and methods: Patients treated with adjuvant CXB following local excision between 2004 and 2017 in three centres were identified (Clatterbridge, Hull, Nice). All patients had adverse pathological features including: lymphovacular invasion, Sm2-3 Kikuchi level, tumour budding, pT2, positive resection margins (R1). CXB was performed with the Papillon50 tm machine to a dose of 40–60 Gy in 2 or 3 fractions over 2–4 weeks preceding/following external beam chemo/radiotherapy. Kaplan Meier survival estimates were used for outcomes measures. Results: 194 patients were identified. Median age was 70 years. pT staging was: pT1:143, pT2:45, pT3:6. CXB alone was given in 24 pts and combined with EBRT in 170. Median follow-up time was 77 months (range 7–122 months). Local relapse rate was 8% and distant metastases 9%. Organ preservation was achieved in 95%. 6 year local recurrence free and overall survival was 91% and 81% respectively. Cancer specific survival was 97%. No treatment related mortality was seen. Conclusion: This large multi-centre cohort study using adjuvant CXB following local excision suggests excellent oncological outcomes for these patients without completion TME. This treatment approach can be considered as an alternative for selective patients compliant with long term follow up.